Enhancing fungal adaptation for efficient caffeine degradation in wastewater: Biomimetic approach and environmental optimization - Bhautik Dave; Ewa Lobos Moysa; Anna Kuźnik (Desalination and Water Treatment)
This study introduces an innovative approach to enhance fungal adaptation and degradation capabilities for treating caffeine, a prevalent environmental pollutant, within wastewater systems. Pure caffeine, extracted from coffee, was thoroughly characterized using Fourier Transform Infrared Spectroscopy (FT-IR) and Nuclear Magnetic Resonance (NMR). The fungal species Trametes versicolor was selected, cultured, and employed in experiments targeting caffeine degradation in potato dextrose broth (PDB) and synthetic wastewater (SWW) media. The caffeine concentration was standardized at 1 mg/10 ml across conditions, with experiments conducted at two temperatures (25 °C and 37 °C) and pH levels (2.5 and 5.18). Additionally, degradation tests were conducted on 100 ml of coffee extract to simulate real-world conditions. Results demonstrated up to 98 % degradation efficiencies under optimized parameters, although higher temperatures and more acidic pH conditions reduced efficacy. Despite some residual compounds observed in NMR spectra, caffeine levels were significantly reduced, achieving 90 % and 98 % degradation rates. These findings underscore the importance of temperature and pH optimization for enhancing caffeine degradation. The methodology leveraged a direct cultivation and adaptation approach for T. versicolor, initiating fungal growth directly from spores within aqueous environments, thereby facilitating its integration into wastewater treatment systems.